Media Crossing Limits: A Study of Media Houses of India - Shakeel, Tahir (Innovative Research Thoughts, 2017)
A democratic system necessitates freedom of the press, which is fundamental to freedom of speech. This right is guaranteed under the Indian Constitution, which includes the Fundamental Right to Freedom of Expression. Individuals' rights are respected by the media, but they must also operate within the parameters of legal principles and laws. In framing these concepts and laws, minimal criteria have been used, and they are not meant to detract from greater protections for free speech. The media1 has an impact on how people perceive and discuss facts in society. The protections of a healthy democracy include media freedom and plurality, as well as criticism of those in authority. The first step toward independence and personal freedom is to keep an eye on and ensure ownership diversity